The Roles of Transparency and Accountability on The Quality of Public Services at the Social Service Office in Pontianak City - Elvina, Dhea Aurellia; Wahyudi, Wahyudi; Wana, Desty; Tarmizi, Tashadi (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
This study aims to determine the effect of transparency and accountability on the quality of public services in the Pontianak City Social Service Office. The population in this study is 695 people who issued complaints at the Social Service Office. Eighty-seven people were involved as samples using simple random sampling techniques. The number of samples was taken using Slovin's formula. A set of questionnaires was distributed as a data collection technique. The data analysis uses multiple linear regression analysis. The t-test results show that the variables of transparency and accountability significantly affected the quality of public services. Meanwhile, the results of the F-test show that transparency and accountability have a significant simultaneous influence on the quality of public services. The coefficient of determination value shows a result of 0.486 which means that this research model can explain the public service quality variable of 48.6%, and other variables can explain the remaining 51.4%.